2013
DOI: 10.5455/oams.090113.br.005
|View full text |Cite
|
Sign up to set email alerts
|

Salivary superoxide dismutase levels in oral leukoplakia and oral squamous cell carcinoma; a clinicopathological study

Abstract: In the SouthEast Asian countries oral cancer is one among the commonly occurring malignancies due to tobacco use and quid chewing habits. Early stage diagnosis of the disease is reported to have a better prognosis. Sialochemistry studies involving antioxidants have recently gained importance as biomarkers for oral cancer risk assessment. The aim of this study was to estimate the levels of superoxide dismutase in saliva of patients with oral cancer, oral leukoplakia and healthy controls. Three study groups comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
5
8
0
Order By: Relevance
“…Shpitzer et al [28] and Shpitzer et al [31] also found total salivary LDH levels to be high in oral cancer patients. Our results are also comparable with the study done by Shetty et al [32] who have reported consistently higher salivary LDH levels in oral precancer and cancer patients as compared to healthy controls.…”
Section: Variablessupporting
confidence: 92%
“…Shpitzer et al [28] and Shpitzer et al [31] also found total salivary LDH levels to be high in oral cancer patients. Our results are also comparable with the study done by Shetty et al [32] who have reported consistently higher salivary LDH levels in oral precancer and cancer patients as compared to healthy controls.…”
Section: Variablessupporting
confidence: 92%
“…The comparison of salivary LDH levels between oral cancer and healthy subjects was statistically significant (p < 0.001). Our study finding was in agreement with the study done by Kallalli et al, 1 Lokesh et al, 8 Shetty et al, 16 Patel and Metgud, 4 and Joshi et al…”
supporting
confidence: 83%
“…The comparison of salivary LDH levels between OSMF and healthy subjects was statistically significant (p < 0.001). Our study findings were consistent with the study conducted by Sivaramakrishnan et al, 3 Kallalli et al, 1 Bhambal et al, 2 Shetty et al, 16 Rathore et al, 9 Pereira et al, 6 and Muralidhar et al 14 According to WHO 2005, oral leukoplakia is defined as a predominantly white patch or plaque that cannot be characterized clinically or pathologically as any other disorder; oral leukoplakia carries an increased risk of cancer development either in or close to the area of leukoplakia or elsewhere in the oral cavity or the head and neck region. 17 Malignant transformation rate of oral leukoplakia varies from 0.13 to 34%.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The enzymatic component includes superoxide dismutase (SOD), peroxidase, catalase (CAT), GST and GPx, while the nonenzymatic component includes uric acid and GSH (43 (44). Enzymes such as SOD are the most effective, intracellular, tumor-suppressing antioxidant enzyme that catalyzes the dismutation of oxygenated free radicals to less-reactive species, and therefore regulates cellular redox state and leads to tumor growth retardation (45). Peroxidase, CAT or GPx prevents carcinogenesis by converting H 2 O 2 produced by SOD into non-harmful molecular oxygen and water (34).…”
Section: Discussionmentioning
confidence: 99%